International agreement as a genre of official style in a historical retrospective (based on materials of agreement of Ukrainian Central Rada) - Гуменяк, Віра Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article is regard an international agreement as a separate genre of the official style on the beginning of the twentieth century during time of the Ukrainian Central Rada activities. Is characterized compositional and linguistic peculiarities of texts of treaties, used legal and official terminology, analyzed lexical, phraseological, morphological peculiarities that reflect the processes of formation the genre of the international agreement and formation of corresponding vocational lexis, accentuated the using of specific Ukrainian lexis. The article stated that in historical retrospective an international treaty is important in the formation of Ukrainian statehood at the beginning of the twentieth century. The conclusion of peace treaties of the UCR is the first attempt to normalize the genre of the treaty in the field of the new Ukrainian language. These documents contain typical elements, accepted language forms, but from the point of view of lexical filling there are many components (lexical, derivational, morphological) that reflect the processes of forming the genre of international treaty.